Transformasi Mobile Learning Sebelum dan Setelah Pandemi Covid-19: Peran Pustakawan dalam Menguatkan Pembelajaran Daring dan Hibrida - Daniel Pandapotan (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the transformation of mobile learning before and after the COVID-19 pandemic and analyzes the evolving role of librarians in strengthening online and hybrid learning in higher education. Using a non-empirical literature-based approach, the research synthesizes recent scholarly works to map structural changes in digital pedagogy, learning models, and information mediation. The findings indicate that mobile learning has shifted from a supplementary instructional tool to a central learning infrastructure that reshapes interaction, access, and knowledge construction. Online and hybrid learning environments demand robust information ecosystems in which librarians function as pedagogical mediators, supporting digital literacy, resource curation, and continuity of learning experiences. Comparative analysis with prior studies reveals that librarian engagement enhances learner autonomy, reduces digital inequities, and improves the sustainability of technology integration. Conceptually, the study positions academic libraries as strategic nodes within digital education systems. The research concludes that effective mobile learning implementation depends on the synergy between technological innovation, institutional design, and librarian-led knowledge facilitation that aligns pedagogical flexibility with academic rigor.